Design and Construction of a Savonius Helix-Type Vertical Axis Wind Turbine Using Computational Fluid Dynamics - Isra' Nuur Darmawan; Kholistianingsih Kholistianingsih; Rahardian Luthfi Prasetyo; Sandhy Dhannova (Vortex, 2026)
This study presents the design, simulation, fabrication, and experimental validation of a Savonius Helix vertical axis wind turbine optimized for low wind regimes in Cilacap, Indonesia. Wind data from NASA POWER were analyzed at two locations, revealing dominant low wind conditions with notable temporal variability. The turbine geometry was optimized based on aerodynamic and inertial parameters, followed by Computational Fluid Dynamics (CFD) simulations to evaluate torque, pressure distribution, and power coefficient across four configurations (2B90P, 2B180P, 3B90P, 3B180P). The optimal design was fabricated using fiberglass and tested under no-load and loaded conditions with a Permanent Magnet DC generator. Results indicate strong agreement between CFD trends and experimental performance, despite deviations caused by mechanical losses and atmospheric turbulence. Overall, the Savonius Helix configuration demonstrates effective energy capture capability in low wind environments, confirming its feasibility for small-scale renewable energy applications.